Social Justice: A Concept Analysis. Issue 2 (23rd August 2016) - Matwick, Angela L.; Woodgate, Roberta L.
Abstract: Social justice is presented frequently as a core or shared value at the very foundation of nursing practice. Despite its acceptance as a core value, its use is varied and there has been inherent difficulty in establishing a definitive explanation for what is meant by social justice. As such, a clearly defined meaning for the concept of social justice does not exist in contemporary nursing literature. Following the method outlined by Walker and Avant, an analysis of the concept of social justice provides clarity to the meaning of social justice as it is used within the nursing profession, in academia, education, and practice.